การก้าวสู่ประชาคมอาเซียน ด้านสังคมและวัฒนธรรมในสถานศึกษา สังกัด ศูนย์การศึกษานอกระบบและการศึกษาตามอัธยาศัย อำเภอแม่สะเรียงจังหวัด - มณีธร นันทวดี (วารสารพุทธศาสตร์ศึกษา, 2018)
The objectives of this thematic paper were 1) to study the preparedness for socio-cultural entry into the ASEAN community in the schools affiliated with the Non-formal Education and Independent Education Center, Mae Sariang District, Mae Nong Son Province, and 2) to study suggestions on the problems and ways to solutions regarding the preparedness for sociocultural entry into the ASEAN community in the schools affiliated with the Non-formal Education and Independent Education Center, Mae Sariang District for a total of Mae Nong Son Province. The research sampling subjects were: one administrator of the schools affiliated with the Non-formal Education and Independent Education Center, Mae Sariang District, one KS 1 KSN and two Tambon KSN teachers, one Tambon coordinating teacher, one public library librarian, one KSN school committee, one KSN student, one public servicereceiver, totaling 10. The data were collected from documents, observation, interview, and group discussion. The data were manipulated and analyzed in descriptive manner.